An equilibrium approach to the disequilibrium in housing market in China - Guan, Mingyang (2014)
The dramatic housing price appreciation in Chinese cities has led to concerns over the emerging housing market disequilibrium and real estate bubbles. This has attracted great attentions from the investors, regulators and researchers. However, in assessing the housing market disequilibrium, very few studies have adopted the widely applied equilibrium asset pricing model in China due to poor data documentation. In this paper, we empirically tested the applicability of equilibrium asset pricing approach with data extracted from 2004 – 2012 Statistical Yearbooks and micro-level matched housing rent-to-price ratios for 60 large and medium-sized Chinese cities in Q4 2013. Together with a fundamental analysis model, we applied this asset approach to examine the premium effects from gender imbalance and credit constraints on Chinese housing capital market, and evaluated cities with “overly high or low” housing prices. With solid estimations and evaluations, we observed little support for gender imbalance and credit constraints to affect the housing prices significantly or robustly. Further investigations concluded that Wenzhou, Shanghai and Beijing seemed to have risks of bubbles, while Guiyang on the contrary seemed to have an under-evaluated housing price.